Hipertrofia muscular de membros inferiores em programas de treinamento com agachamentos: uma revisão sistemática - Paunksnis, Marcos Rodolfo Ramos (2021)
Introduction: Among the various exercises available for prescribing strength training, the squat is one of the most practiced within gyms and training centers, it is an exercise whose performance involves the participation of several joints and muscle groups. Thus, the literature investigates biomechanical changes such as kinetics and kinematics of this exercise. The squat is commonly included in training routines with the most diverse objectives such as gains in strength, power and muscle mass. It is also widely used in rehabilitation programs. Objectives: 1. Analysis of the scientific production of training protocol designs involving the squat exercise. 2. Systematic review of works that involved the squat exercise with four or more weeks of intervention. Methods: 1. Systematic review that evaluated the scientific production between the years 2000 and 2020 of the works that involved the squat exercise and measures of muscular hypertrophy of the lower limbs. 2. Systematic review involving 13 articles between the years 2000 and 2020, involving a total of n = 359 men with and without experience in strength training. The present review was prepared following the recommendations of the Cochrane hanbook of literature for systems reviews and matanalysis. After using the mesh terms used in the PubMed / MEDLINE, Science Direct, Library, Scielo and Scopus databases, a total of 4,223 articles were found. included in this review. Esutodo considerations 1. Regarding the number of publications per year, a peak was observed between the years 2016 and 2020, where Japan and the USA were the countries with the highest number of publications followed by Spain and Brazil, both with the least publications. Pablo de Olavide University located in Spain was responsible for 14% used in this review. Of the articles published, 21% were in the Journal of Strength and Conditioning Research, 21% in the International Journal of Sports Medicine, 14% in Medicine & Science in Sports & Exercise 14% in the European Journal of Applied Physiology, Frontiers in Physiology 1.7%, Applied Physiology Nutrition and Metabolism 1.7%, Scandinavian Journal of Medicine and Science in Sports 1.7% and Journal of Orthopedic & Sports Physical Therapy 1.7% with all journals classified with A1 quails. Considerations for each 2. Studies to date are limited to comparing major and minor ROM. It is possible that the combination of ROM variations could promote complementary effects on lower limb muscle hypertrophy. Therefore, there remains an important gap and lack of consensus in the current literature that requires future exploration.